Administrative Sanction Governance Reform: Optimising the Application of Administrative Sanctions in Indonesia - Rahmawan, Ardianto Budi; Nariswari, Alyca Azka; Sholihah, Afnan Zahidatush (Universitas Brawijaya, 2025)
In previous decades, the Administrative Court (PTUN) was not sufficiently functional to some extent. This article discusses the role of State Administrative Law in operating the oversight and the implementation of administrative sanctions in Indonesia, as well as the issues related to the implementation of administrative sanctions in Indonesia and the implications for public trust. Unlike previous studies that focus solely on the weakness of Indonesia’s administrative sanction system or the general administrative law system in Singapore, this article offers a comparative analysis of administrative reform in Singapore as its compliance and governance have successfully improved. This offer proposes an adaptive framework to optimise Indonesia’s administrative sanction system by taking Singapore’s approach as an example. This article also examines the moment of administrative reform in Singapore and the construction of adopting this reform in Indonesia. By providing an international perspective on administrative sanctions, this study enhances legal science by offering valuable insights for overseas readers on governance reform in developing legal systems and illustrating the role of comparative legal studies in driving institutional improvements beyond national borders. The research method used in this article is normative, utilising secondary data obtained from literature studies. This research uses statutory, case, and comparative approaches. Many cases, however, indicate that administrative sanctions in Indonesia are not properly functioning, leading to ongoing illegal violations and a decline in public trust. Therefore, administrative sanction management in Indonesia requires reform.